Revisão taxonômica do gênero Notiospathius Matthews & Marsh (Hymenoptera: Braconidae: Doryctinae) - Nunes, Juliano Fiorelini (2011)
The taxonomy, despite its recognized importance within biological sciences, has not had the attention it deserves, especially in Brazil and in mega-diverse countries where biodiversity is largely unknown or underestimated. This thesis aims to contribute to the taxonomic knowledge by revising the genus Notiospathius, admittedly speciose in the Neotropics, but not revised yet. The material studied in this work comes from several collections from Brazil and the world and combine a total of 2163 specimens from more than 130 cities in 12 countries. It was made a new and broader diagnosis of the genus. Twenty-six probable new species are described; ten species are registered and their geographic distributions were expanded. The first record of males for six of these species is done. Maps and photos for each species and morphospecies are presented. It was performed an identification key for all morphospecies and for most Notiospathius species. According to this revision, the genus is confirmed as one of the most important within the Subfamily Doryctinae in the Neotropical region in terms of species richness, besides nearly to double the knowledge of it.